Effect of laser surface texturing on friction behaviour in elastohydrodynamically lubricated point contacts under different sliding-rolling conditions. (September 2020) - Boidi, G.; Tertuliano, I.S.; Profito, F.J.; de Rossi, W.; Machado, I.F.
Abstract: The Laser Surface Texturing (LST) technique has been largely investigated to improve the tribological performance of lubricated contacts. The present contribution is aimed at scrutinizing the influence of three texture configurations fabricated by LST on the tribological performance of elastohydrodynamic (EHD) point contacts under different slide-to-roll ratios (SRR), entrainment velocities and inlet temperatures. Friction experiments were conducted through a series of ball-on-disk tests in the MTM-2 (Mini-Traction Machine) tribometer. Main results showed that the texture configurations promoted significant effects under boundary and mixed lubrication conditions, and also affected the full-film EHD regime at higher temperatures. Furthermore, the tribological performance of textured samples was strongly related to the texture depth. Shallower texture designs (∼0.5 μm) reduced friction compared to untextured material, whereas deeper features (>1 μm) generally led to detrimental results. In general, dimples configuration decreased the lift-off speed and promoted full-film EHD conditions for a larger range of speeds, whereas radial curved grooves yielded to friction reduction under mixed lubrication conditions, moving the transition from boundary to mixed regimes to lower speeds, especially for intermediate lubricant viscosity. Highlights: Tribological performance of textured surface in sliding rolling test. Texture depth is a critical factor to be evaluated in EHD lubrication. Dimples configuration decreased lift-off speed, promoting full film conditions. Grooves configuration promoted mixed lubrication regime for larger speed ranges.